Factors influencing engraftment in peripheral autologous haematopoietic stem cell transplantation for lymphoproliferative disease patients in Hospital Universiti Sains Malaysia - Mohamed Fauzi, Hafizuddin (2015)

(untitled)
Introduction: Autologous peripheral blood stem cells transplantation (APBSCT) is a therapeutic option which can be used in various haematological neoplastic disorders. In Hospital Universiti Sains Malaysia (HUSM), APBSCT is practiced in multiple myeloma and lymphoma cases as it is associated with substantial advantages and fewer complications compared to allogenic stem cell transplantation. Objectives: The aim of this study was to identify factors associated with rapid haematopoietic engraftment in lymphoproliferative disease patients undergoing APBSCT. Methodology: A retrospective data analysis was done on lymphoma and multiple myeloma patients treated with APBSCT at HUSM from 2010 until 2013.Data was collected from the record file Haematology Patient Information System (HPIS) in the institution intranet. Twelve factors were analyzed to determine the engraftment time for platelet and neutrophil. Engraftment of neutrophils is defined as count at least 0.5 x 109/L for three consecutive days and platelet count at least 20 x 109/L for seven consecutive days without transfusion support. Early engraftment for both neutrophils and platelet were defined as less than 14 days from the day of stem cell infusion. Data were analyzed using Pearson Chi Square/ Fisher’s Exact and significant factors were analysed with Multiple Logistic Regression test with p < 0.05 indicates statistically significance. Results: Forty patients had been studied, the results showed that 95% patients had successful neutrophil engraftment and 82.5% patients had successful platelet engraftment. From these success groups, the main predictive factor for rapid engraftment for neutrophil is stem cell (CD34+) count while predictive factors that influenced rapid platelet engraftment were (CD34+) count and the stage of the disease at diagnosis. Conclusion: In conclusion, identifying factors that may benefit patients undergoing stem cell transplantation are important and the results obtained can be useful as a guidance to clinical haematologists to optimize their management.